Genome-wide identification and comparative analysis of CCCH-type zinc finger genes in diploid and tetraploid cotton (Gossypium) species - Sun, Gaofei; Dai, Panhong; Tian, Xinquan; Peng, Renhai; Li, Boshen; Ma, Lei; Zhang, Xiaomeng (Frontiers in Plant Science, 2025)
IntroductionCCCH-type zinc finger proteins are important transcriptional regulators involved in plant growth, development, and responses to abiotic stress. Despite their significance, a comprehensive characterization of CCCH genes in cotton is lacking.MethodsWe systematically identified CCCH genes in four cotton species (Gossypium arboreum, G. raimondii, G. hirsutum, and G. barbadense) and performed phylogenetic classification, gene structure, conserved motif, and physicochemical property analyses. Collinearity analyses were conducted to assess gene expansion. Promoter regions were examined for hormone- and stress-responsive cis-elements, and expression profiles were analyzed across tissues, developmental stages, and under abiotic stress conditions.ResultsA total of 183 CCCH genes were identified and grouped into eight phylogenetic clusters. Comparative analyses revealed both evolutionary conservation and lineage-specific diversification. Gene expansion in tetraploid cotton mainly arose from polyploidization, with most genes retained from diploid progenitors, whereas GhCCCH21 and GhCCCH47 were specific to G. hirsutum. Promoter analysis uncovered numerous hormone- and stress-responsive elements, including ABRE, CGTCA-motif, and LTR. Tissue-specific expression patterns showed that GhCCCH24 and GhCCCH14 are preferentially expressed in ovules and fibers, respectively, while GhCCCH23, GhCCCH51, and GhCCCH55 are strongly induced by abiotic stress.DiscussionThese findings reveal the functional diversification of CCCH genes in cotton and identify promising candidates for improving stress tolerance and fiber quality, providing a foundation for future functional studies.